2022
DOI: 10.1213/ane.0000000000005859
|View full text |Cite
|
Sign up to set email alerts
|

The Practice of Pediatric Cardiac Anesthesiology in the United States

Abstract: BACKGROUND: With advances in surgical and catheter-based interventions and technologies in patients with congenital heart disease (CHD), the practice of pediatric cardiac anesthesiology has evolved in parallel with pediatric cardiac surgery and pediatric cardiology as a distinct subspecialty over the past 80 years. To date, there has not been an analysis of the distribution of pediatric cardiac anesthesiologists relative to cardiac and noncardiac procedures in the pediatric population. The primary aim is to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…However, currently, in a survey from Nasr et al sent to 113 pediatric cardiac anesthesia programs, only 38% (117 of 307) of pediatric cardiac anesthesiologists pursued subspecialty training, while the majority gained "on the job" training or alternative training routes. 22 With greater recognition for additional training required to gain the skillset necessary to care for the CHD population, there has been a call to standardize this education. The previous model had been for programs offering an additional year of training in pediatric cardiac anesthesiology to offer their own curriculum of varying lengths and often structured as a faculty-fellow position.…”
Section: The State Of Pediatric Cardiac Anesthesiology In the United ...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, currently, in a survey from Nasr et al sent to 113 pediatric cardiac anesthesia programs, only 38% (117 of 307) of pediatric cardiac anesthesiologists pursued subspecialty training, while the majority gained "on the job" training or alternative training routes. 22 With greater recognition for additional training required to gain the skillset necessary to care for the CHD population, there has been a call to standardize this education. The previous model had been for programs offering an additional year of training in pediatric cardiac anesthesiology to offer their own curriculum of varying lengths and often structured as a faculty-fellow position.…”
Section: The State Of Pediatric Cardiac Anesthesiology In the United ...mentioning
confidence: 99%
“…In that same U.S. survey, 49.2% of institutions were actively recruiting staff. 22 The additional effects of the COVID-19 pandemic on the total number of practicing pediatric anesthesiologists may also increase demand. In a poll sent to all 3245 members of the Society for Pediatric Anesthesiology (SPA) with 561 respondents, Margolis et al found that 10.6% of respondents would reduce their professional working time, and 14.2% planned on retiring earlier while 11.9% planned to retire later.…”
Section: The State Of Pediatric Cardiac Anesthesiology In the United ...mentioning
confidence: 99%
See 1 more Smart Citation
“…4 However, current staffing shortages and staffing paradigms do not always allow for a pediatric cardiac anesthesiologist to be present in the catheterization lab at all times. 6 Until very recently, the field of pediatric cardiac anesthesiology had no formal Accreditation Council for Graduate Medical Education training requirements. Most tertiary care centers have teams of pediatric cardiac anesthesiologists who have acquired training through a multitude of different pathways.…”
mentioning
confidence: 99%
“…The process of how we deliver perioperative care is discussed by 2 papers that examine preanesthesia consultation and the provision of care to young children undergoing cardiac surgery. 4,5 Examining current routine care is also the role of HSR. While much has been published on the need to restrict the use of benzodiazepines because of concerns for delirium and delayed postoperative neurocognitive recovery, Cozowicz et al 6 found that 4 of 5 patients undergoing major orthopedic surgery in the United States receive benzodiazepines perioperatively, and a small but clinically significant proportion of these patients receive long-acting benzodiazepines.…”
mentioning
confidence: 99%